Research and Application of Regenerative Braking Energy Dispatching System for Heavy Haul Railway Traction Power Supply - LIU Zhengxiong; CHEN Ting; CHEN Yin; TIAN Zhe; ZHOU Zhi (Kongzhi Yu Xinxi Jishu)
The regenerative braking energy of heavy haul railway is abundant but poorly utilized, reflected by low regenerative energy quality and poor economic benefit. In order to reduce cost and save energy, a scheme of regenerative braking energy scheduling system for traction power supply of heavy haul railway is proposed. An energy dispatching device is installed in the section post to realize regenerative braking energy scheduling between adjacent substations. In order to maximize energy-saving effect of the energy dispatching device, this paper focuses on the analysis of the traction energy characteristics of substation, and based on the intermittent condition characteristics of energy dispatching between substations. During the intermittent period of the power dispatching device, the pulse output of the multiplex converter is blocked, so as to reduce the no-load loss of the energy dispatching device. The field practical engineering application shows that the reverse electricity utilization rate of the renewable energy dispatching system is more than 50%, and the positive electricity consumption of the traction power supply system is reduced by more than 2%, thus reducing the electricity cost of the railway power supply department.